Uso y valor cultural de la herpetofauna en México: una revisión de las últimas dos décadas (1997–2017) - Ávila-Nájera, Dulce M.; Mendoza, Germán David; Villarreal, Oscar; Serna-Lagunes, Ricardo (Instituto de Ecología, A.C., 2018)
Amphibians and reptiles are vertebrate groups that historically have been used by rural communities. In Mexico, the multiculturalism of the country is closely related to the biological diversity with which it coexists. The use of the Cultural Importance Index (IIC) allows quantify the value of species with different uses and can be useful to focus conservation strategies. The objective of the study was to identify the use and generate an IIC of the herpetofauna, through a bibliometric meta-analysis of publications on the use of Mexican amphibians and reptiles. There were 103 reptiles and 32 amphibians that have at least one use, which varied depending on the taxon (reptiles or amphibians, respectively): food (47, 10), pet (20, 6), commercial (20, 2), ornamental (25, 1), artisan (32, 9), magic-religious (32, 10), medicinal (57, 19), sport hunting (2, 2), damage control (48, 2), beneficial (10, 4). Rhinella marina (27.13) and Crocodylus moreletii (15.42) were the species with the highest IIC. Of the species recorded, 61% and 31% of reptiles and amphibians respectively are in some risk category. It is necessary establish conservation strategies through management and education programs that promote sustainable uses of resources, as well as the conservation of natural spaces where these species inhabit.